2010
DOI: 10.3945/ajcn.2009.28202
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of cocoa product consumption on lipid profile: a meta-analysis of randomized controlled trials

Abstract: Short-term cocoa consumption significantly reduced blood cholesterol, but the changes were dependent on the dose of cocoa consumption and the healthy status of participants. There was no dose response and no effect in healthy participants. Future high-quality studies are needed to determine the efficiency of moderate cocoa consumption on lipid profile in long-term intervention and in subjects with other cardiometabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
1
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 50 publications
9
92
1
10
Order By: Relevance
“…The degree to which LDL and TC levels were reduced in this analysis reflects some measure of potency of the cocoa regimen. Our results are consistent with a similar review (Jia et al, 2010) conducted on eight studies, which reported that intervention with dark chocolate/cocoa products led to LDL reduction by 5.87 mg/dl (À11.13, À0.61 mg/dl) and TC reduction by 5.82 mg/dl (95% CI: À12.39, 0.76 mg/dl) compared with placebo. In addition, we are reporting a nonsignificant reduction in mean serum TG levels by 5.06 mg/dl (95% CI: À13.45, 3.32 mg/dl).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The degree to which LDL and TC levels were reduced in this analysis reflects some measure of potency of the cocoa regimen. Our results are consistent with a similar review (Jia et al, 2010) conducted on eight studies, which reported that intervention with dark chocolate/cocoa products led to LDL reduction by 5.87 mg/dl (À11.13, À0.61 mg/dl) and TC reduction by 5.82 mg/dl (95% CI: À12.39, 0.76 mg/dl) compared with placebo. In addition, we are reporting a nonsignificant reduction in mean serum TG levels by 5.06 mg/dl (95% CI: À13.45, 3.32 mg/dl).…”
Section: Discussionsupporting
confidence: 82%
“…One clinical trial indicated that regular ingestion of dark chocolate may have no adverse effects on serum lipid profile (Crews et al, 2008), whereas others have suggested that intake of dark chocolate reduced serum LDL cholesterol and triglyceride (TG) levels (Engler et al, 2004;Grassi et al, 2005b), and increased serum high-density lipoprotein (HDL) cholesterol measurements (Mursu et al, 2004). An earlier meta-analysis of eight randomized trials involving 215 subjects reported that an intervention with dark chocolate was associated with a significant reduction in serum LDL in subjects with cardiovascular disease risk factors (Jia et al, 2010) compared with placebo. However, that metaanalysis did not assess the effect of dark chocolate or cocoa on serum TG concentrations and it did not include some important recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of cocoa and dark chocolate increase the concentration of HDL cholesterol [229] and plasma antioxidant capacity, decrease the formation of lipid oxidation products, and inhibit the oxidation of LDL [230]. In a meta-analysis study, cocoa was associated with small decreases in total and LDL cholesterol, but not HDL cholesterol concentrations [231]. Cocoa products contain more polyphenols than teas.…”
Section: Chocolatementioning
confidence: 99%
“…A particular group of flavonoids, namely, the flavan-3-ols was found in chocolate (flavanols) [232]. Moderate consumption of cocoa or dark chocolate, have potential health benefits [231], however, a high dose of polyphenols has been shown to exert cytotoxic effects on liver cells [233] and higher polyphenol supplementation may counteract its beneficial biological effects on lipid metabolism [234].…”
Section: Chocolatementioning
confidence: 99%
“…6,7 Current experimental and epidemiological studies provide evidence for a protective role for polyphenol-rich dark chocolate (DC) and cocoa polyphenols on markers of glucose regulation, blood pressure and lipid profile. [8][9][10][11][12][13][14][15][16][17][18] This protective role has been ascribed to the antioxidant properties of DC and cocoa polyphenols and their ability to modulate nitric oxide bioavailability. 14,17 However, few studies have examined the involvement of the endocrine system in mediating the cardiometabolic health-effects of polyphenols.…”
Section: -5mentioning
confidence: 99%